Herpes zoster infection increases the risk of peripheral arterial disease: A nationwide cohort study. Issue 35 (August 2016) - Lin, Te-Yu; Yang, Fu-Chi; Lin, Cheng-Li; Kao, Chia-Hung; Lo, Hsin-Yi; Yang, Tse-Yen
Abstract : Abstract: Varicella-zoster virus infection can cause meningoencephalitis, myelitis, ocular disorders, and vasculopathy. However, no study has investigated the association between herpes zoster (HZ) and peripheral arterial disease (PAD). We identified newly diagnosed HZ from the Taiwan's National Health Insurance Research Database recorded during 2000 to 2010, with a follow-up period extending until December 31, 2011. In addition, we included a comparison cohort that was randomly frequency-matched with the HZ cohort according to age, sex, and index year. We analyzed the risk of PAD with respect to sex, age, and comorbidities by using Cox proportional-hazards regression models. In total, 35, 391 HZ patients and 141, 556 controls were enrolled in this study. The risk of PAD was 13% increased in the HZ cohort than in the comparison cohort after adjustment for age, sex, and comorbidities. The Kaplan–Meier survival curve showed that the risk of PAD was significantly higher in the HZ cohort than in the non-HZ cohort ( P < 0.001). This nationwide population-based cohort study revealed a higher risk of PAD in patients with HZ infection than in those without the infection. Careful follow-up and aggressive treatment is recommended for patients with HZ to reduce the risk of PAD.